â€œEnvironmentally-Friendly Movementâ€ as a Program to Support Sustainable Development Goals Using Text Mining Methods - Indriyani Rachman; Anna Permanasari; Toru Matsumoto (Yayasan Keluarga Guru Mandiri, 2022)
Nowadays, environmental initiatives and campaign activities are promoted massively in Bandung City. These activities are part of the program to achieve sustainable development goals at the municipal level. Text mining methods from online news and media were conducted to understand the implication of the program to the pro-environmental behavior and consciousness of the Bandung City residents. A questionnaire survey to 340 residents of Bandung City was also distributed randomly to see the relationship between sociodemographic profiles (age and education level) and pro-environmental behavior of the respondents. Results showed that the Kang Pisman program became the highest environmentally friendly movement program promoted through mass media. This result also correspondence to the questionnaire survey in which people in Bandung City try to reduce their produced waste. Besides, education level is insignificant, and age becomes one-factor influencing environmental behavior. The interesting point is that the government should enhance organic waste management since many people are unwilling to process their organic waste. To promote, educate, and engage residents in pro-environmental behavior, stakeholders should conduct environmentally friendly movements, thus achieving local SDGs target.